Morphological features of stromal-vascular component of the thymus of stillborn children and children under one year of life from mothers that do not follow a healthy lifestyle. - Gorianikova, I. N. (Морфологія / Morphologia / Morfologìâ, 2015)
Background. Morphofunctional state of the thymus of child in most cases is directly dependent on the mother health and her lifestyle. Objective. The purpose of the research was to reveal the morphological features of stromal-vascular component of the thymus of stillborn children and children under one year of life born from women who conducted a sedentary lifestyle, smoked, drank alcohol and ate the foods containing tartrazine. Methods. The material of the study was 67 thymuses of stillborn children and children under one year of life born from mothers who conducted a sedentary lifestyle, smoked, drank alcohol and ate the foods containing tartrazine. Results. It was found that the above mentioned components of mother lifestyle are damaging factors for thymus of their children that lead to structural changes in the walls of microcirculatory blood vessels, circulatory disorders, sclerotic and atrophic changes in the organ. Structural changes in the vascular endothelium (swelling, desquamation), wall of the vessel (focal thickening of the basement membrane, thickening of the vessel wall), sclerotic and atrophic processes in the thymus increased with increasing age of the child. The severity of the circulatory disorders (vascular hyperemia, hemorrhage, edema, thrombus formation) decreased with increasing age of the child. Conclusion. An important step to prevent the structural changes in children from mothers with unhealthy lifestyles is pregravid preparation including conscious following the rules of healthy lifestyle, formation the moral responsibility and willingness to pregnancy.